Analisis Pengelolaan Data Morbiditas 10 Besar Penyakit pada Pasien Rawat Jalan di Rumah Sakit X - Putri Zeniawati; Ade Irma Suryani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Implementing a reporting flow is important for hospitals, because it functions as a management guide and policy to anticipate unexpected situations. Having a flow will make it easier for officers to carry out their work and implementing the flow will encourage officers to be more disciplined and responsible in their work. The aim of this study was to determine the difficulties experienced in managing, collecting data and input reporting the morbidity of the top 10 diseases in outpatients. Qualitative descriptive research. The subjects were the head of medical records, 2 medical records officers and 2 reporting officers. As a result, reporting is carried out by the responsible reporting officer, data collection is in accordance with standard operational procedures, data processing is computerized by the assigned reporting officer and sent via online SIRS to the Health Service at the beginning of each year. Trends in the top 10 diseases in hospitals include viral infections, dyspepsia, dengue fever, diarrhea, bacterial infections, anxiety disorders, radiculopathy, asthma, pulpitis and GERD.